2020
DOI: 10.1088/1755-1315/462/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of proximate composition and vitamin C of Physalis angulata Linn and Physalis peruviana Linn in West Java, Indonesia

Abstract: This study aimed to evaluate the proximate and vitamin C of Physalis. Two species of Physalis, namely, P. angulata L. and P. peruviana L., used as models for a comparative study. Proximate composition, fiber, and vitamin C of all part of Physalis, i.e., leaf, stem, bud, and fruit of Physalis were analyzed. Physalis angulata collected from Pagaden subdistrict (latitude: 6030’24” S, longitude: 107048’74”E, elevation: 55 MAMSL) Subang District, West Java Province, and Physalis peruviana collected from Pamulihan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…Moisture content of the amala was found higher than in the study of Iwansyah et al [22] but it was similar to the findings of Parveen and Khatkar [23]. Total ash, crude protein, crude fiber and carbohydrate of the amala were similar to the findings of Iwansyah et al [22] but in the study of Parveen and Khatkar [23], crude fiber was found higher. Some of the parameters were similar and some were different when compared to the study of Khattak [24].…”
Section: Nutritional and Chemical Composition Of The Fresh Amala Fruitsupporting
confidence: 83%
“…Moisture content of the amala was found higher than in the study of Iwansyah et al [22] but it was similar to the findings of Parveen and Khatkar [23]. Total ash, crude protein, crude fiber and carbohydrate of the amala were similar to the findings of Iwansyah et al [22] but in the study of Parveen and Khatkar [23], crude fiber was found higher. Some of the parameters were similar and some were different when compared to the study of Khattak [24].…”
Section: Nutritional and Chemical Composition Of The Fresh Amala Fruitsupporting
confidence: 83%
“…Nutritional and Chemical analysis Moisture content of the amala was similar to the findings of (Parveen & Khatkar, 2015). Total ash, crude protein, crude fiber and carbohydrate of the amala (Table 2) were similar to the findings of (Iwansyah et al, 2020) but in the study of (Parveen & Khatkar, 2015) crude fiber was found higher. Some of the parameters were similar and some were different when compared to the different researches (Khattak, 2013).The pH and TSS were similar to the findings of (Kulkarani, Pandey, Sharma, & Joshi, 2017;Ranote, Hothe, & Bawa, 2002).…”
Section: Resultssupporting
confidence: 79%
“…20-30 mg 100 g -1 (Akhtar et al, 2010;Ahmad et al, 2015;Du Yu-dan et al, 2017). It was high in cutleaf groundcherry than muskmelon 7.74 -13.32 mg 100 g -1 (Lin et al, 2004), strawberry 16-27 mg 100 g -1 (Li et al, 2017) and Physalis peruviana 9-19 mg 100 g -1 (Ariati et al, 2017;Iwansyah et al, 2019). An antioxidant content in PA 01-PA 09 was 56.45-58.70% (Table 3), the consistant results was reported by Yildiz et al (2015), that was recorded 57-59%.…”
Section: Quality Characteristics Of Cutleaf Groundcherrymentioning
confidence: 62%